2019
DOI: 10.1021/acs.jpcb.8b12172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of 2-Aminopurine-Labeled Dinucleoside Monophosphates Reveal Multiscale Stacking Kinetics

Abstract: Molecular dynamics (MD) simulations of 2-aminopurine (2Ap)-labeled DNA dinucleoside monophosphates (DNMPs) were performed to investigate the hypothesis that base stacking dynamics occur on timescales sufficiently rapid to influence the emission signals measured in time-resolved fluorescence experiments. Analysis of multiple microsecond-length trajectories shows that the DNMPs sample all four coplanar stacking motifs. In addition, three metastable unstacked conformations are detected. A hidden Markov-state mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 89 publications
1
6
0
Order By: Relevance
“…83 Recently, it has been shown that conformational transformations in RNA oligonucleotides are multi-time-scale phenomena, which occur within the range of a few nanoseconds to 80 ns. 84 It has also been argued that the heterogeneous decay of fluorescence signals in RNA DNMPs labeled with 2-aminopurine (2Ap) is an indication of the variability of stacked structures. 85 Furthermore, femtosecond spectroscopy has shown the importance of the RNA ability to adopt multiple stacked states, especially in a highly dynamic structure like a tetraloop.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…83 Recently, it has been shown that conformational transformations in RNA oligonucleotides are multi-time-scale phenomena, which occur within the range of a few nanoseconds to 80 ns. 84 It has also been argued that the heterogeneous decay of fluorescence signals in RNA DNMPs labeled with 2-aminopurine (2Ap) is an indication of the variability of stacked structures. 85 Furthermore, femtosecond spectroscopy has shown the importance of the RNA ability to adopt multiple stacked states, especially in a highly dynamic structure like a tetraloop.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We observe that the dynamical fingerprinting approach presents an elegant means to compare experimental relaxation data directly against a Markov state model extracted from simulation data in terms of a "fingerprint" of peaks with amplitudes and time scales related to the relaxation of particular system observables. 122 These techniques have been previously employed to in applications to base stacking of DNA dinucleoside monophosphates 123 and RNA. 92 We explored the use of this approach to validate the MD simulation data but encountered challenges in resolving fast dynamical motions below the lag time of the fitted MSM and the extremely high computational cost of collecting sufficient simulation data to fit MSMs at each temperature for which experimental data was collected.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical modifications in the presented non-canonical bases were assigned by analog using existing bond and dihedral types. The full set of RESP-fitted charges of the nine non-canonical bases, parameterized for parmbsc1 are given in Table S5, Supplementary Materials , with literature values [ 29 , 30 , 31 , 32 , 33 , 34 ] where available. Parenthetically, an inspection of Table S5 shows the RMS deviations between our charges and those from the literature to be on the same order of magnitude, and in the same direction, as the differences between charges derived from QM-based models for the canonical residues in parm94 (c.f., Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%